Más allá de la Captura del Estado: formas híbridas de estatalidad desde el caso subregional del Catatumbo – Colombia - Ortega Palacio, Henry Yesid (2019)
Multiple studies address the state in Colombia as a special case in Latin America, among many reasons, due to the particular coexistence of a long and apparently stable democracy accompany with prolonged periods of armed violence and regional marginality. For the Colombian case, Luis Jorge Garay has been a key author in the use of the notion of Capture of the State while others, like Fernán González, propose contrary readings that try to approach the question from concepts such as differentiated Presence of the State and hybrid Governance. The present research gathers these discussions, opting preferably for the second author in mention, to give a general perspective of the hybridity and the own forms of governability in regions where the state is, first of all, another player in the constant disputes of power.As a basis for these discussions, the research takes Catatumbo as a case, a region marked by the conflict in northeastern Colombia. There, a current tremble caused by the disarmament of the Farc put in dispute the political orders generated by armed groups - still belligerent - and the civilian population through strong social movements and the State. The findings show the particular ways of power in regions of these characteristics with the possibility of extending these analytical elements to other cases in the country and the rest of Latin America.